Description of the mature larva of Ampulicomorpha schajovskoyi De Santis & Vidal Sarmiento (Hymenoptera: Embolemidae) - Guglielmino, Adalgisa; Bückle, Christoph (Zootaxa, 2013)
The mature larva of Ampulicomorpha schajovskoyi De Santis & Vidal Sarmiento, 1977, is described and figured for the first time. Larval characters of Dryinidae and Embolemidae are discussed in regard to possible synapomorphies of each family and of both families together (Dryinidae + Embolemidae) as monophyletic groups. Some larval characters are com-pared with the corresponding conditions in other Chrysidoidea families.